Publishing within open science challenges - Antunes, Maria Da Luz (2019)
This chapter relates the diffusion of scientific knowledge, materialized in its writing, publication, and circulation, with the Open Science. Open Science is, by its nature, a platform for dialogue, fostering more exchanges and stimulating researchers to adapt their publishing and dissemination practices, leading to cost reduction and enhancement of academic content and fostering greater circulation and knowledge generation. The purpose is the accomplishment of proposals regarding the actions that researchers must take in the scope of scholarship as conversation, namely, embedding academic writing in Open Science and sharing research data and results. Finally, we reflect on current Open Science challenges to researchers and academia.